Macroscopic bursting in physiological networks: node or network property?. (May 2015) - Ferrari, Fabiano A S; Viana, Ricardo L; Gomez, Florian; Lorimer, Tom; Stoop, Ruedi
Abstract Activity pattern modalities of neuronal ensembles are determined by node properties as well as network structure. For many purposes, it is of interest to be able to relate activity patterns to either node properties or to network properties (or to a combination of both). When in physiological neural networks we observe bursting on a coarse-grained time and space scale, a proper decision on whether bursts are the consequence of individual neurons with an inherent bursting property or whether we are dealing with a genuine network effect has generally not been possible because of the noise in these systems. Here, by linking different orders of time and space scales, we provide a simple coarse-grained criterion for deciding this question.